Moans and groans – logical walkthrough of a patient journey from renal failure to parathyroid carcinoma. (24th May 2012) - Poole, R; Jamil, F; Owen, CJ; Tse, Y
Abstract : Aim: Parathyroid carcinoma is vanishingly rare in childhood and the presenting symptoms are often vague and varied. While orphan diseases are individually rare, and clinicians may only encounter each one once in their career, together they form a significant volume of paediatric practice. We aim to demonstrate a patient journey of this rare condition and illustrate how through basic principles the diagnosis was reached logically. Case: A 14 year old boy with no significant past medical or family history presented after a short history of painful frank haematuria. Obstructive renal failure from urolithiasis was diagnosed and relieved. Directed diagnostic workup, starting from first principles revealed hypercalcaemia and hypercalciuria resulting from hyperparathyroidism. Further directed investigations revealed a solitary parathyroid nodule. After parathyroidectomy he required management of hypocalcaemia from expected hungry bone syndrome. Histological examination finally revealed parathyroid carcinoma. Workup for multiple endocrine neoplasia syndromes was negative. Conclusion: Our case illustrates that rare conditions in children can be diagnosed and managed using a logical stepwise approach. Although rare diagnoses are seldom encountered, a structure approach using basic principles can be helpful for all clinical problem solving.